Aspects of Bloomsbury - Rosenbaum, S. author. aut Link
XI, 215 p.
Keywords: Much of the widespread interest in the Bloomsbury Group over the past quarter-century has been biographical, yet without the Group's works there would be little interest in their lives. The studies in literary and intellectual history and collected in this volume are chiefly concerned with these works. Subjects covered in the eight essays include an analysis of the philosophical assumption of Virginia Woolf's fiction, an assessment of J M Keyne's account of D H Lawrence's reactions to Cambridge, discussions of the literary backgrounds of E M Forster's Aspects of the Novel and Virginia Woolf's A Room of One's Own , a consideration of the Woolfs' work as printers and publishers, and a history of Ludwig Wittgenstein's relations with the Bloomsbury Group.